Pharmacodynamics and pharmacokinetics of Danshen in isoproterenol-induced acute myocardial ischemic injury combined with Honghua. (30th January 2020) - Qu, Cheng; Xu, Ding-Qiao; Yue, Shi-Jun; Shen, Le-Fei; Zhou, Gui-Sheng; Chen, Yan-Yan; Wang, Xiao-Ping; Bai, Ji-Qing; Liu, Feng; Tang, Yu-Ping; Zhao, Bu-Chang; Duan, Jin-Ao
Abstract: Ethnopharmacological relevance: Herb pair, the most fundamental and simplest form of herb compatibility, serves as the basic building block of traditional Chinese medicine formulae. The Danshen–Honghua herb pair (DH), composed of Salviae Miltiorrhizae Radix et Rhizoma (Danshen in Chinese) and Carthami Flos (Honghua in Chinese), has remarkable clinical efficacy to cure cardio-cerebrovascular diseases. This study was designed to investigate the pharmacodynamics of DH in comparison with single herbs and pharmacokinetics of DH relative to Danshen in acute myocardial ischemic injury. Materials and methods: Sixty male Wistar rats were divided into control, model and drug treated groups. The acute myocardial ischemia rat model was induced by administering 85 mg/kg/d isoproterenol (ISO) subcutaneously for two consecutive days. For pharmacodynamic study, histopathological and biochemical analysis were performed to assess the anti-myocardial ischemic effects. While for pharmacokinetic study, a UPLC–MS/MS method was developed for determination of nine main active ingredients, namely danshensu, protocatechuic acid, protocatechualdehyde, caffeic acid, lithospermic acid, rosmarinic acid, salvianolic acid B, salvianolic acid A and salvianolic acid C in rat plasma. Results: The histopathological and biochemical analysis revealed that DH exerted enhanced anti-myocardial ischemic effects against the ISO-induced myocardial ischemia compared with single herbs. The pharmacokinetic study indicated that DH could significantly increase the t 1/2z of danshensu, T max, AUC0-∞ and MRT0-t of protocatechuic acid in comparison with Danshen alone in normal rats, but more importantly elevate systemic exposure level and prolong t 1/2z of protocatechualdehyde, caffeic acid, T max of danshensu in acute myocardial ischemia rats. Conclusions: Our findings demonstrated the greater effects of DH after the compatibility in ISO-induced acute myocardial ischemia rats at pharmacodynamic and pharmacokinetic levels and provided valuable information for clinical application of herb pairs. Graphical abstract: Image 1